RISK ASSESSMENT OF OVERHEAD CRANE (OHC) DOUBLE GIRDER OPERATION IN THE KAPAL NIAGA DIVISION IN PT PAL INDONESIA (PERSERO) - Novita, Lenny; Nawawinetu, Erwin Dyah (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: PT PAL Indonesia (Persero) operates Overhead Crane Double Girder tool everyday. The operation of the device have some risk of material hazard, material pinched, material scratched, fracture and passed away. Purpose: The purpose of this research was to assess the level of risk of occupational injury on the operation of Overhead Crane Double Girder. Method: This research was a descriptive observational one. This study focuses on the operation of Overhead Crane Double Girder in the Kapal Niaga division PT PAL Indonesia (Persero) which consist of the preparation and operation phase. Result: The initial risk level categorized as high-risk level of 44% and a moderate risk level of 56%. The most frequently prevention measure ware routine check, compliance of SOP and PPE usage on workers. Implementation of control efforts resulted in a moderate risk rate of 44% and a low risk level of 56%. Conclusion: Recommendation of control for PT PAL Indonesia (Persero) performs routine maintenance both on equipment and overhead crane function double girder, application and compliance of operating SOP, and operator must have driving license of overhead crane double girder and experience in the field, if applied properly then final risk level to be 100% low.